2000
DOI: 10.1603/0022-0493-93.3.763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insecticides on the Diamondback Moth (Lepidoptera: Plutellidae) and Its Parasitoid <I>Diadegma insulare</I> (Hymenoptera: Ichneumonidae)

Abstract: Studies were conducted to evaluate the toxicity of insecticides to adult Diadegma insulare (Cresson) and its host the diamondback moth, Plutella xylostella (L.). Leaf-dip and direct-dip bioassays for diamondback moth larvae and residual bioassays for adults of diamondback moth and D. insulare were used to assess mortalities. Larval mortalities at field rates were significantly higher with carbaryl, permethrin, spinosad, and tebufenozide when compared with Bacillus thuringiensis, or imidacloprid in the larval-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 11 publications
3
30
1
5
Order By: Relevance
“…* As médias seguidas pela mesma letra minúsculas na linha (para comparação entre dose e subdose de cada inseticida para cada espécie), maiúsculas na coluna (para comparação da seletividade dos inseticidas dentro de uma mesma concentração) ou minúsculas e em itálico na linha (para comparação entre tolerância das espécies à uma mesma concentração de cada inseticida), não diferem, entre si, pelo teste de Scott -Knott, a P < 0,05. crisântemo. Já Bacci et al (2002) Metamidofós 600 CE 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa Paratiom metílico 600 CE 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa Carbaril 850 PM 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa (HILL & FOSTER, 2000).…”
unclassified
“…* As médias seguidas pela mesma letra minúsculas na linha (para comparação entre dose e subdose de cada inseticida para cada espécie), maiúsculas na coluna (para comparação da seletividade dos inseticidas dentro de uma mesma concentração) ou minúsculas e em itálico na linha (para comparação entre tolerância das espécies à uma mesma concentração de cada inseticida), não diferem, entre si, pelo teste de Scott -Knott, a P < 0,05. crisântemo. Já Bacci et al (2002) Metamidofós 600 CE 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa Paratiom metílico 600 CE 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa Carbaril 850 PM 100,00 0,00 aAa 100,00 0,00 aAa 100,00 0,00 aAa (HILL & FOSTER, 2000).…”
unclassified
“…Cordero et al (2007) observed Ϸ80% mortality of D. insulare after 24 h at the Þeld-use rates of spinosad. Hill and Foster (2000) reported spinosad caused 100% mortality of D. insulare 8 h after treatment under laboratory conditions. However, in a follow-up study, parasitism of P. xylostella larvae was not affected by spinosad application under Þeld conditions (Hill and Foster 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Their results indicated that Cry1C Bt broccoli plants and the puriÞed Cry1C toxin had no direct toxicity to D. insulare. Chen et al (2008) and Hill and Foster (2000) observed no survival of adult parasitoids directly treated with spinosad. Chen et al (2008) observed no survival of adult parasitoids directly treated with lambda-cyhalothrin.…”
Section: Methodsmentioning
confidence: 97%